2013
DOI: 10.1136/bjophthalmol-2013-304024
|View full text |Cite
|
Sign up to set email alerts
|

New light for old eyes: comparing melanopsin-mediated non-visual benefits of blue-light and UV-blocking intraocular lenses

Abstract: Phacoemulsification, particularly first-eye surgery, has a strong positive effect on cognition and daytime alertness, regardless of IOL type.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 23 publications
3
21
0
Order By: Relevance
“…This is in concordance with previous questionnaire-based studies (Ayaki et al 2013(Ayaki et al , 2014Wei et al 2013;Schmoll et al 2014) and on meta-analysis (ref review). Sleep efficiency increased significantly exclusively for participants allocated to blue-blocking IOLs and WASO decreased (improved) for the entire population.…”
Section: Neutral Iolsupporting
confidence: 92%
“…This is in concordance with previous questionnaire-based studies (Ayaki et al 2013(Ayaki et al , 2014Wei et al 2013;Schmoll et al 2014) and on meta-analysis (ref review). Sleep efficiency increased significantly exclusively for participants allocated to blue-blocking IOLs and WASO decreased (improved) for the entire population.…”
Section: Neutral Iolsupporting
confidence: 92%
“…Recently two investigators 41,42 reported that sleep quality significantly improved in cataract cases implanted with blue light-blocking IOLs, based on the survey with questionnaire, and their results supported our previous results with blue light-blocking IOLs. 4 In terms of the IOL color, a clear lens has greater light transmittance than a yellow-colored IOL and thus the effect on circadian rhythm synchronization may be stronger.…”
Section: Discussionsupporting
confidence: 79%
“…[17][18][19]66 Cataract surgery for the main part is carried out in an elderly population in whom there is an age-related decline in retinal photoreceptors and ganglion cell populations, as well as the function of the circadian clock, and with ageing smaller pupils. It is clear that access to light is important for this group.…”
Section: Discussionmentioning
confidence: 99%
“…17 It has already been shown in a number of studies that in addition to improving vision, cataract surgery has been shown to lead to an improved sleep-wake pattern. [17][18][19]66 This benefit is presumed due to the increased amount of light reaching the retina. Landers et al 66 carried out a cross-sectional study comparing the sleep quality of 31 individuals with UVB-IOL and 18 individuals with BFIOL.…”
Section: Age-related Macular Degeneration and Iol Typementioning
confidence: 99%
See 1 more Smart Citation